Impact of Soil Improvers on Soil Health: A Data Mining Approach to Support Sustainable Agriculture Across the EU - Nolfi, Lorenzo; Bindo, Arianna; Di Gregorio, Luciana; Costanzo, Manuela; Caldara, Marina; Tabacchioni, Silvia; Visca, Andrea; Salo, Tapio; Bauerle, Andrea; Hansen, Veronika; Bernini, Roberta; Varese, Giovanna Cristina; et al. (MDPI, 2025)
Soil health is crucial for the sustainability of agricultural practices and ecosystem resilience. Using a data mining approach, this study aims to explore emerging themes related to the impact of soil improvers on soil health by analyzing results from various EU-funded agricultural projects, with the final goal of identifying the key factors driving the effectiveness of soil amendments. By integrating data mining and text analysis, the study extracts, aggregates, and visualizes insights, providing a comprehensive overview of innovative strategies to enhance soil fertility and promote ecological balance. This integrated analytical framework offers a nuanced understanding of the conceptual landscape surrounding soil health in EU projects, highlighting the multifaceted roles of organic amendments and microbial solutions. Our findings underscore the critical link between organic amendments and soil health, highlighting their potential as strategic tools for achieving more sustainable agricultural systems. These findings provide a basis for refining soil management strategies in agriculture and support the development of evidence-based policies aimed at improving soil health and fostering ecological balance across Europe.
Keywords: soil health; soil improvers; organic amendments; microbial solutions; EU projects; sustainable agriculture; data mining